2016
DOI: 10.1016/j.homp.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

What do homeopathic doctors think of vaccines? An international online survey

Abstract: The results show that there is no contradiction between homeopathy and primary prevention by means of vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Likewise, a multinational study of physicians practicing homeopathy, 77% of whom came from Latin American countries, found that 75.6% considered vaccination safe, effective, and necessary, although 12.5% would not recommend it under any circumstance [49]. Some studies have shown similar results specifically for vaccination against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a multinational study of physicians practicing homeopathy, 77% of whom came from Latin American countries, found that 75.6% considered vaccination safe, effective, and necessary, although 12.5% would not recommend it under any circumstance [49]. Some studies have shown similar results specifically for vaccination against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Eine Analyse aus dem Jahr 2016 [11] von Eizayaga und Waisse aus Südamerika kam zu einem ähnlichen Ergebnis. Von den 512 befragten Ärzten stammten 77,5 % der Befragten aus lateinamerikanischen Ländern, 16,8 % aus Spanien und eine geringe Anzahl aus mehreren anderen Ländern.…”
Section: Aktuelle Situationunclassified
“…Respondents from Brazil, where homeopathy is officially recognised, were more favourable than respondents from countries where homeopathy is not so recognised. 9…”
Section: Attention Deficit Hyperactivity Disorder (Adhd) Hay Feveranmentioning
confidence: 99%